A Study of Indoor Air Quality in Refurbished Museum Building - Syahrun Neizam Mohd Dzullkiflli; Abd Halid Abdullah; Lee Yee Yong; Abdul Mutalib Leman; Samiullah Sohu (Salehan Institute of Higher Education, 2018)
Problem related with indoor air quality (IAQ), is rapidly becoming a major health issue as people spend almost 90% of their time indoors. Museums were established in Malaysia more than hundred years ago. Since the year 2005, Malaysia has been moving away from constructing new buildings in favour of refurbishing historic and old ones. A healthy environment at the museum building has been identified as one of the important element that must been considered, but it is not sure either IAQ in the museum building provide a good air quality or not. The purpose of this study is to determine the actual indoor environment of the museum building in Melaka. In this study, the IAQ measurement were conduct for six days at the Melaka Sultanate Palace Museum and at the History and Ethnography Museum. During the measurement, IAQ parameters of gaseous pollutant of nitrogen dioxide, sulfur dioxide and carbon dioxide, and particulate matter of fine particles were recorded by using specific IAQ equipment. The finding of this study indicates that the distance of buildings from roadways appears to have an impact on indoor environmental levels, especially for nitrogen dioxide, sulfur dioxide and particulate matter. Based on the results, only gaseous pollutant of sulfur dioxide had not exceeding the acceptable TLV compared to the other IAQ pollutants.